2018
DOI: 10.1155/2018/9281286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-Hydroxymethylcytosine Epigenetic Modification on the Stability and Molecular Recognition of VEGF i-Motif and G-Quadruplex Structures

Abstract: Promoters often contain asymmetric G- and C-rich strands, in which the cytosines are prone to epigenetic modification via methylation (5-mC) and 5-hydroxymethylation (5-hmC). These sequences can also form four-stranded G-quadruplex (G4) or i-motif (iM) secondary structures. Although the requisite sequences for epigenetic modulation and iM/G4 formation are similar and can overlap, they are unlikely to coexist. Despite 5-hmC being an oxidization product of 5-mC, the two modified bases cluster at distinct loci. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…This is probably due to the poor binding affinity of DNMT1 toward 5hmC, suggesting that 5hmC, as opposite to 5meC, could promote DNA demethylation by excluding DNMT1 from CpG islands [105]. In human stem cells, a very small fraction of G4s harbors 5hmeC in loop regions, and the presence of this modification does not markedly affect G4 formation or stability [106,107]. On the other hand, it has been shown that the oxidized derivatives of cytosine dynamically recruit distinct sets of regulatory proteins in differentiating mouse embryonic stem cells, suggesting that G4-associated cytosine modifications epigenetically influence the propensity of G4 structures to be recognized by DNA-binding effector proteins [108].…”
Section: Interplay Between G4 Structures and Epigenetic Modifications Of Dna Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the poor binding affinity of DNMT1 toward 5hmC, suggesting that 5hmC, as opposite to 5meC, could promote DNA demethylation by excluding DNMT1 from CpG islands [105]. In human stem cells, a very small fraction of G4s harbors 5hmeC in loop regions, and the presence of this modification does not markedly affect G4 formation or stability [106,107]. On the other hand, it has been shown that the oxidized derivatives of cytosine dynamically recruit distinct sets of regulatory proteins in differentiating mouse embryonic stem cells, suggesting that G4-associated cytosine modifications epigenetically influence the propensity of G4 structures to be recognized by DNA-binding effector proteins [108].…”
Section: Interplay Between G4 Structures and Epigenetic Modifications Of Dna Basesmentioning
confidence: 99%
“…On the other hand, it has been shown that the oxidized derivatives of cytosine dynamically recruit distinct sets of regulatory proteins in differentiating mouse embryonic stem cells, suggesting that G4-associated cytosine modifications epigenetically influence the propensity of G4 structures to be recognized by DNA-binding effector proteins [108]. Recent studies focused on the G4 from the vegf promoter have revealed that this is indeed the case, where the presence of 5meC significantly decreases the binding ability of the VEGF165 protein, while 5hmeC specifically abrogates nucleolin recruitment [107,109,110].…”
Section: Interplay Between G4 Structures and Epigenetic Modifications Of Dna Basesmentioning
confidence: 99%
“…Accounting for the presence of epigenetic modifications on iMs may be crucial to understanding the role of these dynamic conformers in gene regulation. For example, the presence of 5hmCs and on iMs could not only alter the conformation and stability of these structures, but also alter their recognition by transcription factors and other biological molecules [28]. From our study, we conclude that very few iM-forming gene sequences have 5hmCs associated within putative iM structures.…”
Section: Introductionmentioning
confidence: 69%
“…For example, Sprujit et al [21] demonstrated that different 5-modified cytosine derivatives (5mC, 5hmC, 5-formylcytosine, and 5-carboxycytosine) are recognized by distinctly different sets of transcription regulators and DNA-repair proteins in mouse ESC. In addition, we recently reported that 5hmC modification of the G4 from the VEGF promoter abrogates its recognition by nucleolin [28]. Hence, it may be imperative to account for the presence of 5hmC or other 5-substituted cytosines in loops of G4s and within iMs while studying gene regulation by these structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study from Morgan, et al exploring the impact of 5-hydroxymethylcytosine (5-hmC) on the G4 within the VEGF promoter may provide insight. In general, G4 oligonucleotides containing a 5-hmC modification at different loop locations did not disrupt G4 formation, according to circular dichroism analysis [88]. VEGF G4 wildtype and 5-hmC containing oligonucleotides were also incubated with the G4 stabilizer TMPyP4 or the protein nucleolin, whose ability to bind G4s has been established.…”
Section: Base Oxidation In Loop Sequencesmentioning
confidence: 99%